Addition of Platinum Derivatives to Fluoropyrimidine-Based Neoadjuvant Chemoradiotherapy for Stage II/III Rectal Cancer: Systematic Review and Meta-Analysis. (11th May 2019) - Hüttner, Felix J; Probst, Pascal; Kalkum, Eva; Hackbusch, Matthes; Jensen, Katrin; Ulrich, Alexis; Debus, Jürgen; Jäger, Dirk; Diener, Markus K
Abstract: Background: Current guidelines recommend neoadjuvant therapy for patients with stage II or III rectal cancer. The addition of platinum derivatives to fluoropyrimidine-based chemoradiotherapy has been frequently investigated, but their role in this setting remains controversial. Methods: PubMed, Cochrane Library, and Web of Science were systematically searched for randomized trials comparing chemoradiotherapy with or without platinum agents in stage II or III rectal cancer. Main outcome parameters were overall and disease-free survival, additional outcomes included pathological complete response, isolated local recurrence, distant recurrence, toxicity, and perioperative morbidity. Time-to-event data were pooled as hazard ratios (HRs) by the inverse variance method and binary outcomes as odds ratios (ORs) by the Peto method with their respective 95% confidence interval (CI). All statistical tests were two-sided. Results: Ten randomized controlled trials with data on 5599 patients were included in the meta-analysis. Platinum derivatives did not statistically significantly improve overall survival (HR = 0.93, 95% CI = 0.82 to 1.05, P  =   .23), disease-free survival (HR = 0.91, 95% CI = 0.83 to 1.01, P  =   .07), or local recurrence (OR = 0.83, 95% CI = 0.66 to 1.05, P  =   .12). However, it led to a statistically significant increase of pathological complete response (OR = 1.31, 95% CI = 1.10 to 1.55, P  =   .002) and a statistically significant reduction of distant recurrence (OR = 0.78, 95% CI = 0.66 to 0.92, P  =   .004). Benefits were accompanied by higher rates of grade 3 or 4 toxicities. Conclusions: Intensified neoadjuvant chemoradiotherapy with the addition of platinum derivatives cannot be recommended routinely because it did not improve overall or disease-free survival and was associated with increased toxicity. It needs to be elucidated whether the benefits in distant recurrence and pathological complete response may be advantageous for selected high-risk patients.